Hormonal contraception increases risk of breast tumor based on clinical breast examination among adult women - Darjoko, Sulistyowati Tuminah; Sapardin, Aprildah Nur (Universa Medicina, 2017)
BackgroundIn Indonesia, cancer prevalence according to the Basic Health Research 2013 was 1.4 per 1000 inhabitants and the most common cancer in hospitalized patients in 2010 was breast cancer (28.7%). Hormonal contraception (HC) use increases the breast cancer risk, even though HC has been used by 210 million women in the world. We aimed to define the association of HC with breast tumors based on clinical breast examination (CBE).MethodsA case-control design using secondary data from the baseline of the Cohort Study on the Risk Factors of Non-Communicable Disease (RFNCD) in 2011-2012 in 5 villages in Central Bogor District, Bogor City. Samples consisted of 152 cases and 152 controls. Cases comprised palpable tumors in one or both breasts CBE (+). Controls had no tumors in both breasts /CBE(-). Data were analyzed by logistic regression.ResultsOdds Ratio (OR) of CBE + was 1.83 (95% CI: 1.11-3.04; p=0.019) for HC user and 1.62 (95% CI: 1.01-2.60; p=0.044) for blood total cholesterol level <200 mg/dL. OR of group CBE(+) was 1.01 (current smoking) and 0.49 (former smoking) compared with nonsmoking (p=0.082); OR was also 1.21 for subjects with one child and 1.77 for those without children, compared with those who had Â³2 children (p=0.454).Conclusion Hormonal contraception use increases breast tumor risk 1.8-fold after controlling for total cholesterol, smoking status and parity. With the several limitations of this advanced analysis, investigations focused on types and duration of HC use are still necessary.